2014
DOI: 10.1021/cg501226v
|View full text |Cite
|
Sign up to set email alerts
|

Designing Functional Metal–Organic Frameworks by Imparting a Hexanuclear Copper-Based Secondary Building Unit Specific Properties: Structural Correlation With Magnetic and Photocatalytic Activity

Abstract: In continuation of our research interest in pyrazole-based multifunctional metal organic frameworks (MOFs), we report here three Cu(II) MOFs using pyrazole and various aromatic carboxylic acid-based ligands. The main theme of interest is to design functional MOFs by imparting a multinuclear metal center as a secondary building unit (SBU). Accordingly, three MOFs are synthesized based on a hexanuclear Cu-pyrazolate unit as the SBU with some intriguing structural networks like (4,4) type herringbone grid or an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(46 citation statements)
references
References 57 publications
1
45
0
Order By: Relevance
“…For example, the socalled secondary building unit (SBU) concept, which involves the identification of ar obusta nd reproducibleb uildingb lock as av ertex and subsequent construction of an etwork by linking them with organic ligandso fw ell-definedg eometry,i sa n effective route to synthesize and design MOFs. [38,93] OH)) n (MOF-3) by using the multinuclear Cu-pyrazolate system as aS BU by as olvothermalm ethod under similarc onditions, where Pyz = 1 H-pyrazole, NAPH = 1,4-naphthalene dicarboxylic acid, BIPH = biphenyl-4,4'-dicarboxylic acid, and PDC = 3,4-pyridinedicarboxylic acid. [38] It was found that the three MOFs have intriguing structural networks like a( 4,4)-type herringboneg rid or an archetypal Kagome topology,a nd the planar Cu-pyrazolate moiety with open metal sites or loosely bound solventm olecule offers an excellent platform for photocatalysis.T he band gap energies of MOF-1, MOF-2, and MOF-3 are calculated to be 3.87, 2.03, and2 .00 eV,r espectively.Such band gap sizes of MOFs 1-3 imply that the samples may have potentialr esponses to light for photocatalyticr eactions.…”
Section: Pure Mof Photocatalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the socalled secondary building unit (SBU) concept, which involves the identification of ar obusta nd reproducibleb uildingb lock as av ertex and subsequent construction of an etwork by linking them with organic ligandso fw ell-definedg eometry,i sa n effective route to synthesize and design MOFs. [38,93] OH)) n (MOF-3) by using the multinuclear Cu-pyrazolate system as aS BU by as olvothermalm ethod under similarc onditions, where Pyz = 1 H-pyrazole, NAPH = 1,4-naphthalene dicarboxylic acid, BIPH = biphenyl-4,4'-dicarboxylic acid, and PDC = 3,4-pyridinedicarboxylic acid. [38] It was found that the three MOFs have intriguing structural networks like a( 4,4)-type herringboneg rid or an archetypal Kagome topology,a nd the planar Cu-pyrazolate moiety with open metal sites or loosely bound solventm olecule offers an excellent platform for photocatalysis.T he band gap energies of MOF-1, MOF-2, and MOF-3 are calculated to be 3.87, 2.03, and2 .00 eV,r espectively.Such band gap sizes of MOFs 1-3 imply that the samples may have potentialr esponses to light for photocatalyticr eactions.…”
Section: Pure Mof Photocatalystsmentioning
confidence: 99%
“…[38,93] OH)) n (MOF-3) by using the multinuclear Cu-pyrazolate system as aS BU by as olvothermalm ethod under similarc onditions, where Pyz = 1 H-pyrazole, NAPH = 1,4-naphthalene dicarboxylic acid, BIPH = biphenyl-4,4'-dicarboxylic acid, and PDC = 3,4-pyridinedicarboxylic acid. [38] It was found that the three MOFs have intriguing structural networks like a( 4,4)-type herringboneg rid or an archetypal Kagome topology,a nd the planar Cu-pyrazolate moiety with open metal sites or loosely bound solventm olecule offers an excellent platform for photocatalysis.T he band gap energies of MOF-1, MOF-2, and MOF-3 are calculated to be 3.87, 2.03, and2 .00 eV,r espectively.Such band gap sizes of MOFs 1-3 imply that the samples may have potentialr esponses to light for photocatalyticr eactions. MOF-3 exhibitsh igherm ethylene blue (MB) and methyl orange (MO) photodegradation efficiency than MOF-1 and MOF-2 under UV irradiation with H 2 O 2 addition owing to the discrepancy of their band gap energies (E g )r esulting from the structuraldifference.…”
Section: Pure Mof Photocatalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the previously reported Cu II ‐based photocatalysts with high‐performance degradation ability towards RhB and MO, such as {[Cu II (SalImCy)](Cu I I) 2 · DMF} n [SalImCy = N , N ′‐bis[(imidazol‐4‐yl)methylene]cyclohexane‐1,2‐diamine], {[Cu 3 (μ 3 ‐OH)(μ‐Pyz) 3 (PDC)(H 2 O) 2 (CH 3 OH)] n (HPyz = 1H‐pyrazole and H 2 PDC = 3,4‐pyridinedicarboxylic acid), [(CH 3 ) 2 NH 2 ][Cu(BPT)] · DMF · 2H 2 O (H 3 BPT = biphenyl‐3,4′,5‐tricarboxylic acid), {[Cu 5 (μ 8 ‐L1) 2 (μ 3 ‐OH) 2 (H 2 O) 5 ] · 4.5DMF · 18H 2 O} n (L1 = 3‐(3′,5′‐dicarboxylphenoxy) phthalic acid), {[Cu 9 (OH) 6 Cl 2 (itp) 6 (1,4‐bdc) 3 ](NO 3 ) 2 (OH) 2 · 20H 2 O} n [itp = 1‐imidazol‐1‐yl‐3‐(1,2,4‐triazol‐4‐yl)propane and 1,4‐bdc = 1,4‐benzenedicarboxylate], [Cu 3 (L 2 )(NO 3 ) 4 (H 2 O) 4 ] n (HL 2 = pyridine‐2,6‐dicarbohydrazide based imine‐linked ligands), {[Cu 4 (OH) 2 (bix) 2 (1,2,4‐btc) 2 (H 2 O) 2 ] · 3H 2 O} n [bix = 1,4‐bis(2‐methyl‐imidazol‐1‐ylmethyl)benzene and 1,2,4‐btc = 1,2,4‐benzenetricarboxylate], and [Cu(4,4′‐bipy)Cl] n (4,4′‐bipy = 4,4′‐bipyridine), the unsaturated central Cu II atom with the coordination numbers ranged from 3 to 5 and the lower band‐gap (1.07 eV) dominated by the bulky conjugated‐backbone of the organic ligand play important roles for the enhancement of the photocatalytic activity of 1 …”
Section: Resultsmentioning
confidence: 99%
“…Metal‐organic frameworks (MOFs), which are self‐assembled from organic linkers and inorganic connectors of metal ions and/or clusters, are a new type of crystalline porous materials that has shown potential applications in various fields, such as photocatalysis,15 gas storage separation,6 photoluminescence,7–10 and chemical sensing 11–14. Recently, much effort has been exerted on the syntheses of luminescent porous MOFs for their potential applications in the green degradation of organic dyes, which was one of the major pollutants in water for their long lifetime and wide distribution 1517. Thus, the appropriate choice of chemically modified organic ligands and functional central metal atoms to construct functional porous MOFs is highly necessary for degradation of organic dyes under light irradiation 18,19.…”
Section: Introductionmentioning
confidence: 99%